'Wir sind das Volk!' Representative Claim-Making and Populist Style in the PEGIDA Movement's Discourse. Issue 4 (1st October 2020) - Volk, Sabine
Abstract : This study examines the processes of representative claim-making in populist discourse, tying in with discursive-performative approaches to political representation, populism and social movements. The theoretical framework integrates Saward's constructivist theory of representation and Moffitt's approach to populism as a political style. It develops contentious repertoires, stages, mise-en-scène, scripts, audiences and constituencies as analytical categories for the study of populist claim-making processes. Focusing on the Dresden-based right-wing populist 'Patriotic Europeans against the Islamization of the Occident' (PEGIDA) as a case study, the paper carries out a discourse-based analysis of PEGIDA's claim to represent the people (' Wir sind das Volk! ') in the movement's early phase (2014/15). In line with the emphasis on the theatrical and symbolic dimensions of contentious politics, the analysis highlights the various performative and aesthetic strategies which PEGIDA employs to make its representative claim resonate with its audiences and constituencies. Overall, this study reveals the conceptual and analytical complexity of claim-making performances which construct the category of the people rather than simply claiming its representation.